Student reasoning in organic chemistry : research advances and evidence-based instructional practices - Graulich, Nicole, 1982-; Shultz, Ginger (Cambridge, UK : Royal Society of Chemistry, 2023)
Reasoning about structure-reactivity and chemical processes is a key competence in chemistry. Especially in organic chemistry, students experience difficulty appropriately interpreting organic representations and reasoning about the underlying causality of organic mechanisms. As organic chemistry is often a bottleneck for students' success in their career, compiling and distilling the insights from recent research in the field will help inform future instruction and the empowerment of chemistry students worldwide. This book brings together leading research groups to highlight recent advances in chemistry education research with a focus on the characterization of students' reasoning and their representational competencies, as well as the impact of instructional and assessment practices in organic chemistry. Written by leaders in the field, this title is ideal for chemistry education researchers, instructors and practitioners, and graduate students in chemistry education.
Students' Attention on Curved Arrows While Evaluating the Plausibility of an Organic Mechanistic Step / Melissa Weinrich and Ryan Britt -- Supporting Spatial Thinking in Organic Chemistry Through Augmented Reality : An Explorative Interview Study / Sebastian Keller and Sebastian Habig -- Representational Competence Under the Magnifying Glass : The Interplay Between Student Reasoning Skills, Conceptual Understanding, and the Nature of Representations / Lyniesha W. Ward, Fridah Rotich, Julia Hoang and Maia Popova -- Fostering Causal Mechanistic Reasoning as a Means of Modelling in Organic Chemistry / Olivia M. Crandell and Melanie M. Cooper -- Students' Reasoning in Chemistry Arguments and Designing Resources Using Constructive Alignment / Jacky M. Deng, Myriam S. Carle and Alison B. Flynn -- From Free Association to Goal-directed Problem-solving : Network Analysis of Students' Use of Chemical Concepts in Mechanistic Reasoning / Gyde Asmussen, Marc Rodemer, Julia Eckhard and Sascha Bernholt -- Epistemic Stances in Action : Students' Reasoning Process While Reflecting About Alternative Reaction Pathways in Organic Chemistry / Leonie Lieber and Nicole Graulich -- How Do Students Reason When They Have to Describe the "What" and "Why" of a Given Reaction Mechanism? / Jolanda Hermanns and David Keller -- In-the-moment Learning of Organic Chemistry During Interactive Lectures Through the Lens of Practical Epistemology Analysis / Katie H. Walsh, Jessica M. Karch and Ira Caspari-Gnann -- Flipped Classrooms in Organic Chemistry : A Closer Look at Student Reasoning Through Discourse Analysis of a Group Activity / Suazette R. Mooring, Nikita L. Burrows and Sujani Gamage -- Systemic Assessment Questions as a Means of Assessment in Organic Chemistry / Gulten Sendur -- Variations in the Teaching of Resonance : An Exploration of Organic Chemistry Instructors' Enacted Pedagogical Content Knowledge / Emily L. Atieh, Jherian K. Mitchell-Jones, Dihua Xue and Marilyne Stains -- Investigation of Students' Conceptual Understanding in Organic Chemistry Through Systemic Synthesis Questions / Tamara Rončević, Dušica D. Rodić and Saša A. Horvat -- Disciplining Perception Spatial Thinking in Organic Chemistry Through Embodied Actions / Mike Stieff, Stephanie Scopelitis and Matthew Lira -- Building Bridges Between Tasks and Flasks : Design of a Coherent Experiment-supported Learning Environment for Deep Reasoning in Organic Chemistry / Andreas Trabert, Catharina Schmitt and Michael Schween -- Assessment of Assessment in Organic Chemistry : Review and Analysis of Predominant Problem Types Related to Reactions and Mechanisms / Gautam Bhattacharyya -- Developing Machine Learning Models for Automated Analysis of Organic Chemistry Students' Written Descriptions of Organic Reaction Mechanisms / Field M. Watts, Amber J. Dood and Ginger V. Shultz -- Development of a Generalizable Framework for Machine Learning-based Evaluation of Written Explanations of Reaction Mechanisms from the Post-secondary Organic Chemistry Curriculum / Jeffrey R. Raker, Brandon J. Yik and Amber J. Dood -- The Central Importance of Assessing "Doing Science" to Research and Instruction / Cara E. Schwarz, Kimberly S. DeGlopper, Aubrey J. Ellison, Brian J. Esselman and Ryan L. Stowe.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 05, 2023).
eBooks on EBSCOhost
Keywords: Chemistry, Organic -- Study and teaching; Reasoning -- Study and teaching; Chemistry, Organic; Chemistry, Organic -- Research; Chimie organique; Chimie organique -- Recherche; Chimie organique -- Étude et enseignement; organic chemistry; Chemistry, Organic; Chemistry, Organic -- Research